Sistem Monitoring Limbah Oli Menggunakan Arduino Uno Berbasis Lora - Adi Galih Utomo; Diana Alia; Anak Agung Istri Sri Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
Oil is one of the essential lubricating materials for machinery, especially on ships. With the abundant use of oil, waste oil is generated from the remaining oil discharge, causing dirty oil to become waste oil. To monitor the disposal of waste oil by ships,